1982
DOI: 10.2172/6779066
|View full text |Cite
|
Sign up to set email alerts
|

Fire-Protection Research for Energy-Technology Projects: FY 1981 year-end report

Abstract: Prepared for US-DOE Assistant Secretary for Environment, Safety and Emergency Preparedness; Office of Operational Safety, Washington, DC 20545r--.T. '. r ''*"• I;;JKS1 IS UNIIMIUI msci.-miER I hK document »as prepared as an account of «ork sponsored !»\ an agenct of the I nited Stales < internment. Neither I fit-I niled Slates t.oternmenl nor the I niu-rsit> of ( alifomia nor any of their emjlotecs. makes anv warrant*, express or implied, or assumes anv legal liability or responsibility for the accurao. com pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In moderate-temperature pyrolysis of various wire and cable insulations, the insulations form detectable amounts of light hydrocarbons in the very early degradation '-tage. 1 Our GC/MS analyses of the liquid pyrolyzates from these insu lations show no unique components of specific in sulations that can help in choosing fire-resistant cables. The data, however, can be used to isolate those insulations that incorporate flammable plasticizers; such plasticizers enhance the insulations' flammability so that flame retardants should be incorporated if the plasticizers are used in the insulations.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In moderate-temperature pyrolysis of various wire and cable insulations, the insulations form detectable amounts of light hydrocarbons in the very early degradation '-tage. 1 Our GC/MS analyses of the liquid pyrolyzates from these insu lations show no unique components of specific in sulations that can help in choosing fire-resistant cables. The data, however, can be used to isolate those insulations that incorporate flammable plasticizers; such plasticizers enhance the insulations' flammability so that flame retardants should be incorporated if the plasticizers are used in the insulations.…”
Section: Discussionmentioning
confidence: 81%
“…The rest of the testing followed the procedure reported in last year's report. 1 Fire Chemistry: Thermal Degradation of Cable and Wire Insulations Experimental Results Teflon Polytetrafluoroethylene (Teflon), used in smallsignal wire insulations, is one of the most stable addition polymers, owing to the strength of the C-F bond and the shielding effect of the highly electronegative fluorine atoms. Reaction involves random-chain scission followed by depolymerization and chain termination by disproportionation, 71 " although it has been suggested that, in stead of an unzipping mechanism, CF 2 fragments are eliminated which subsequently combine in the gas phase to give tetrafluoroethylene.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations